Distinct but overlapping binding sites of agonist and antagonist at the relaxin family peptide 3 (RXFP3) receptor - Wong, Lilian L. L. (J Biol Chem, 2018)
The relaxin-3 neuropeptide activates the relaxin family peptide 3 (RXFP3) receptor to modulate stress, appetite, and cognition. RXFP3 shows promise as a target for treating neurological disorders, but realization of its clinical potential requires development of smaller RXFP3-specific drugs that can penetrate the blood–brain barrier. Designing such drugs is challenging and requires structural knowledge of agonist- and antagonist-binding modes. Here, we used structure–activity data for relaxin-3 and a peptide RXFP3 antagonist termed R3 B1–22R to guide receptor mutagenesis and develop models of their binding modes. RXFP3 residues were alanine-substituted individually and in combination and tested in cell-based binding and functional assays to refine models of agonist and antagonist binding to active- and inactive-state homology models of RXFP3, respectively. These models suggested that both agonists and antagonists interact with RXFP3 via similar residues in their B-chain central helix. The models further suggested that the B-chain Trp(27) inserts into the binding pocket of RXFP3 and interacts with Trp(138) and Lys(271), the latter through a salt bridge with the C-terminal carboxyl group of Trp(27) in relaxin-3. R3 B1–22R, which does not contain Trp(27), used a non-native Arg(23) residue to form cation–π and salt-bridge interactions with Trp(138) and Glu(141) in RXFP3, explaining a key contribution of Arg(23) to affinity. Overall, relaxin-3 and R3 B1–22R appear to share similar binding residues but may differ in binding modes, leading to active and inactive RXFP3 conformational states, respectively. These mechanistic insights may assist structure-based drug design of smaller relaxin-3 mimetics to manage neurological disorders.